PENGARUH PENDIDIKAN ORANG TUA DAN LINGKUNGAN SEKOLAH TERHADAP MOTIVASI BELAJAR SISWA SMK NEGERI 3 TANJUNGPINANG - Billy Christian Simamora; Moch Solikin (Department of Automotive Engineering Education, Faculty of Engineering, Yogyakarta State University, 2024)
The purpose of this research is to find out: 1) the effect of parental education on learning motivation of class XI students of the Automotive Engineering Expertise Program at SMK Negeri 3 Tanjungpinang; 2) the influence of the school environment on the learning motivation of class XI students of the Automotive Engineering Expertise Program at SMK Negeri 3 Tanjungpinang; 3) the influence of parental education and the school environment on the learning motivation of class XI students of the Automotive Engineering Expertise Program at SMK Negeri 3 Tanjungpinang. This research is a causal associative research using a quantitative approach. Test the validity of the instrument using Pearson Product Moment and test the reliability using Alpha Cronbach with the help of SPSS software version 29 for Windows. The analysis assumption test consists of a normality test, linearity test, multicollinearity test and heteroscedasticity test. Test the hypothesis using simple regression and multiple regression. The results showed that 1) there was a positive and significant effect of parental education on learning motivation with tcount (3.154) > ttable (1.997) at a significant level of 5% and contributing 13.1% to learning motivation. 2) there is a positive and significant effect of the school environment on learning motivation with tcount (4.297) > ttable (1.997) at a significant level of 5% and contributing 21.9% to learning motivation. 3) there is a positive and significant effect of parental education and the school environment on learning motivation with fcount (13.512) > ftable (3.14) at a significant level of 5% and contributing 29.4% to learning motivation.